Challenges faced by Dairy producers for Pursing Sustainable Livelihood in Mullaithivu District - Shivany, A.; Sathana, V.; Piriya, M. (University of Jaffna, 2016)
Dairy farming contributes to the rural economy by the way of production of organic fresh milk, milk based products, and the addition to the supply of draught power (bio-gas). It also ensures the supply of valuable nutrients and provides self-employment opportunities to the people. The fresh milk production identified in Mullaitivu as a livelihood source and uplift the living standards of resettled families through government and non-government projects. This district was badly affected by the thirty-year conflict, which ended in May 2009. People were subjected to multiple displacements and numerous lost their livelihoods. Several people in Mullaithivu district have transformed their livelihoods, for their subsistence. Many rumors stated that the dairy farmers in this district have bearable livelihood, but in real it has not been accomplished, even though they are experienced in dairying and crop agriculture, and many assistances were offered. This study focuses to identify the challenges faced by dairy producers for pursing that level. Data were collected from 35 dairy farmers through Participatory Rural Appraisal Method (PRA) via qualitative methodology. This applied marketing researched categorized the challenges as marketing problems, investment problems, problems for managing cattle, lack of research in dairy production, social and cultural barriers, and the lack of networking system. There are many weaknesses identified at the farmers' level for achieving their target. Lack of integrated system in dairy sector management in post conflict areas should be linked in into a social network system for managing livelihood at the sustainable level.
Keywords: Dairy producers; Participatory Rural Appraisal (PRA); Sustainable-livelihood